Changes in mood state and recovery-stress perception after an HRV-guided running program in untrained women - Fernandes da Silva, Danilo; Morais Peixoto, Evandro; Michael Ferraro, Zachary; Adamo, Kristi Bree; Machado, Fabiana Andrade (Revista de Psicología del Deporte (Journal of Sport Psychology), 2020)
To determine the effects of HRV-guided running training on mood state and recovery-stress factors in untrained women. Thirty untrained women were randomized into two groups. The CG performed a pre-defined training program while the HRVG completed their running training regarding the intensity distribution according to the parasympathetic activity. The questionnaires of perception of recovery-stress and mood state were answered pre and post-training. The CG reported reduced emotional stress (-0.8±1.3), conflicts/pressure (-0.8±0.8), and increased sleep quality (0.9±1.1), personal acceptance (0.9±1.6), self-regulation (0.8±1.3), specific recovery mean (0.6±0.9), and total recovery mean (0.4±0.7). The HRVG reported decreased general stress (-0.5±0.8), emotional stress (-0.7±1.2), social stress (-0.8±1.0), lack of energy (-0.8±0.8), general stress mean (-0.5±0.8), and increased self-regulation (0.7±1.1). This group also decreased tension (-2.8±3.7), depression (-2.7±4.2), anger (-2.8±4.4) and fatigue (-2.7±3.7) and TMD (-10.7±14.2). HRVG reduced negative scales of mood state and stress factors that were not observed in the controls.